Pelatihan Pembelajaran Kooperatif Pada Guru PAI - Wawan Samudera, Alfan Hadi, Andrian Firdaus, Samsul Hakim (KREASI : Jurnal Inovasi dan Pengabdian kepada Masyarakat, 2021)
This study aims to provide cooperative learning training for PAI teachers. The sample in this study were PAI teachers at MTs Al Amin Gersik Kediri. This type of research is descriptive. Based on the results of the study, it was concluded that this training could have a significant effect on the teaching ability of PAI teachers using cooperative learning.